2005
DOI: 10.1093/jac/dki202
|View full text |Cite
|
Sign up to set email alerts
|

Linezolid: low pre-treatment platelet values could increase the risk of thrombocytopenia

Abstract: Shigella sonnei and Salmonella enterica serotype Typhimurium isolates producing CTX-M b-lactamases as causes of community-acquired infection in France. Clin Infect Dis 2005; 40: 1069-70. 5. Jacoby GA, Han P. Detection of extended-spectrum b-lactamases in clinical isolates of Klebsiella pneumoniae and Escherichia coli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
19
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 5 publications
4
19
1
Order By: Relevance
“…The reported incidence of linezolid-induced thrombocytopenia varies, ranging from 7.5 to 48% according to the definition of thrombocytopenia [13][14][15][16][17]. Birmingham et al [17] reported that thrombocytopenia occurred in 7.5% of patients, with the mean time to 50% reduction of the platelet count being 2-3 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence of linezolid-induced thrombocytopenia varies, ranging from 7.5 to 48% according to the definition of thrombocytopenia [13][14][15][16][17]. Birmingham et al [17] reported that thrombocytopenia occurred in 7.5% of patients, with the mean time to 50% reduction of the platelet count being 2-3 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study in patients receiving short-course linezolid therapy, Grau et al [11] found that a low pre-treatment platelet count was an independent factor associated with moderate to severe thrombocytopenia. In our study, we found no differences in the pre-treatment platelet count between the patients who developed thrombocytopenia and those who did not.…”
Section: Discussionmentioning
confidence: 99%
“…Linezolid treatment is associated with reversible thrombocytopenia, particularly when used for Ն14 days (2,(5)(6)(7). Patients with baseline platelet counts of 241 ϫ 10 9 /liter or less (8) and renal insufficiency (9) are at particular risk for linezolid-induced thrombocytopenia. In this context, implementing systematic monitoring programs (10) and predicting and minimizing the extent of platelet decline in high-risk patients is important.…”
mentioning
confidence: 99%